ARTISTIC DEPICTION OF FEMALE TRAGEDY IN ERKIN AZAM'S SHORT STORIES (American Journal of Pedagogical and Educational Research, 2023)
This article analyzes the short stories "Zabarjad" and "Parizod" by the writer E.Azam, one of the bright figures of the Uzbek literature of the period of independence, and talks about the essence of the tragedy of women and the factors influencing its emergence.